Tinjauan Yuridis Mengenai Perjanjian Pra-Nikah Dalam Prespektif Hukum Perdata di Indonesia: A Legal Review of Prenuptial Agreements from a Civil Law Perspective in Indonesia - Annisa Candra Dewi; Hartono; Zulkifli (Journal of Indonesian Comparative of Syari'ah Law, 2026)
Prenuptial agreements in the Indonesian legal system occupy a complex position at the intersection of contractual freedom and normative limitations within family law, which is inherently influenced by moral and religious values. This study aims to analyze the permissible scope of clauses in prenuptial agreements and to examine the legal consequences arising from breach of such agreements. This research employs a normative juridical method, utilizing statutory and conceptual approaches, and is supported by empirical data obtained through interviews with legal practitioners. The findings indicate that prenuptial clauses are generally valid insofar as they do not contravene mandatory legal provisions, public morality, or religious norms. Clauses regulating property separation, debt liability, and protective non-economic aspects, such as anti-domestic violence commitments and monogamy agreements, are considered valid provided they meet the requirements set forth in Article 1320 of the Indonesian Civil Code. Conversely, clauses that infringe upon fundamental marital rights, violate inheritance law, or contradict Islamic legal principles are deemed null and void. A breach of a prenuptial agreement gives rise to multidimensional legal consequences, including grounds for divorce, claims for damages, and implications for third parties, particularly in relation to property and debt. This study underscores the necessity of clearer normative parameters to ensure legal certainty and fairness in the formulation and enforcement of prenuptial agreements.